1998
DOI: 10.3141/1630-08
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Aggregate Gradation on Fatigue Life of Asphalt Concrete Mixes

Abstract: Four-point bending fatigue tests following the Strategic Highway Research Program (SHRP) M009 test protocol were executed to investigate to what extent gradation has an effect on fatigue performance of asphalt aggregate mixes. Gradations and mixes were selected that would satisfy all volumetric Superpave designs passing below the restricted zone. Other mixes were prepared with gradations passing through and above the restricted zone. The measured fatigue lives of 130 actual laboratory tests were compared with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
3

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(20 citation statements)
references
References 0 publications
0
15
0
3
Order By: Relevance
“…Estudos publicados na literatura relatam a importância das propriedades dos agregados minerais no comportamento mecânico de misturas asfálticas, tanto com relação à resistência à deformação permanente (Masad et al, 2003;Souza, 2009;Bessa, 2012), quanto com relação à resistência ao trincamento por fadiga (Monismith, 1970;Sousa et al, 1998;Vasconcelos, 2004;Masad et al, 2005). Esse comportamento está diretamente relacionado a propriedades de forma dos agregados minerais (forma, angularidade e textura) e a distribuição granulométri-ca da mistura asfáltica.…”
Section: Introductionunclassified
“…Estudos publicados na literatura relatam a importância das propriedades dos agregados minerais no comportamento mecânico de misturas asfálticas, tanto com relação à resistência à deformação permanente (Masad et al, 2003;Souza, 2009;Bessa, 2012), quanto com relação à resistência ao trincamento por fadiga (Monismith, 1970;Sousa et al, 1998;Vasconcelos, 2004;Masad et al, 2005). Esse comportamento está diretamente relacionado a propriedades de forma dos agregados minerais (forma, angularidade e textura) e a distribuição granulométri-ca da mistura asfáltica.…”
Section: Introductionunclassified
“…Simulating the fatigue behavior of hot mix asphalt (HMA) has been done using different test methods over the past 40 years, with varying success [3][4][5][6][7][8][9][10]. Tangella et al [11] listed the general categories of different test methodologies which included: simple flexure, supported flexure, diametral test, triaxial test, direct axial test, fracture test, and wheel tracking test.…”
Section: Introductionmentioning
confidence: 99%
“…Gradations passing above the restricted zone were concluded to be the least favorable. The HMA mixtures with gradations plotting above or through the restricted zone were reported to have better fatigue performance than gradations passing below the restricted zone (Sousa et al, 1998). Haddock et al (1999) concluded that both 9.5-and 19.5-mm (0.375-and 0.75-inch) NMAS mixtures with gradations passing above the restricted zone have higher strengths than those with gradations passing below the restricted zone.…”
Section: Influence Of Modified Binder On Pavement Propertiesmentioning
confidence: 99%